The narrative language of youth offenders with callous and unemotional traits: A corpus analysis - Bowman, Luana (Legal and criminological psychology, 2023)
Purpose This study examined the specific language features that youth offenders express during autobiographical narratives, and tested whether offenders with high levels of callous and unemotional (CU) traits exhibit those language features known to be associated with psychopathic traits in adult offenders. These include increased instrumental and self-oriented language, and decreased cohesiveness and fluency. A further aim was to test whether language-related correlates of CU traits are consistent among offenders and non-offenders. Methods Participants were 130 males participants aged 13-to-20 years, comprising offender and non-offender samples. Data collection involved an interview-based autobiographical narrative task, and self-reports on the Inventory of Callous Unemotional Traits. Using a corpus comparison method, narrative transcripts were coded with linguistic analysis software (Wmatrix) and compared for youth with high versus low levels of CU traits in both samples. Results Compared to youth offenders with low levels of CU traits, high-CU offenders used more physiological need language (e.g. references to food, money), and used fewer cohesive conjunctions (e.g. ‘because’, ‘and’), indicating increased instrumental language, and decreased cohesiveness. Low-CU offenders also used more discourse marker disfluencies than high-CU offenders. No differences were found for social need language or other disfluencies, and no associations between CU traits and language were found among non-offenders. Conclusions Youth offenders with high levels of CU traits exhibit unique language features when expressing autobiographical narratives. Findings point to potential developmental differences in how these features present in adolescence versus adulthood. Furthermore, these features may be somewhat specific to youth whose CU traits co-occur with delinquency.